The comprehension and production of Wh- questions among Malay children with developmental language disorders: Climbing the syntactic tree - Abu Bakar, Norsofiah; Smith, Giuditta; Razak, Rogayah A.; Garraffa, Maria (Frontiers in Psychology, 2022)
This study is an investigation of both comprehension and production of Wh- questions in Malay-speaking children with a developmental language disorder (DLD). A total of 15 Malay children with DLD (ages 7;0–9;11 years) were tested on a set of Wh- questions (who subject and object, which subject and object), comparing their performance with two control groups [15 age-matched typically developing (TD) children and 15 younger TD language-matched children]. Malay children with DLD showed a clear asymmetry in comprehension of Wh- questions, with a selective impairment for which NP questions compared with who questions. Age-matched controls performed at ceiling in all Wh- questions, while the language-matched group reported a subject/object asymmetry selective for the which NP, as reported in other languages. In production, both children with DLD and younger children showed a preference for questions with in situ Wh- elements, a structure that is allowed in colloquial Malay, but which is not produced by the age-matched TD group. Several non-adult-like strategies were adopted particularly by the children with DLD to avoid complex sentences, including substitution with yes/no echo questions, production of the wrong Wh- question, and use of a generic Wh- element. The study provides an insight on the mastery of Wh- questions in both typical Malay children and children with DLD. Implications for the definition of a clinical marker for DLD in a free word order language with Wh- in situ option will be discussed.